Nitrous oxide decomposition over Al2O3 supported noble metals (Pt, Pd, Ir): Effect of metal loading and feed composition. Issue 2 (June 2015) - Pachatouridou, Eleni; Papista, Eleni; Iliopoulou, Eleni F.; Delimitis, Andreas; Goula, Grammatiki; Yentekakis, Ioannis V.; Marnellos, George E.; Konsolakis, Michalis
Graphical abstract: Highlights: The de-N2 O performance of Al2 O3 -supported noble metals (Pt, Pd, Ir) is explored. The impact of metal loading and oxygen presence in feed stream is investigated. The superior performance of Pd and Ir catalysts, compared to Pt, is demonstrated. PdO and IrO2 phases, not easily susceptible to oxygen poisoning, are formed. Metallic Pt 0 species are prone to poisoning by strongly adsorbed oxygen. Abstract: The N2 O decomposition (de-N2 O) performance of Al2 O3 supported, low content (0.25, 0.5 and 1.0 wt.%) noble metal (Pt, Pd, Ir) catalysts, is comparatively explored in the present study. The effect of metal content, operation temperature and feed composition on de-N2 O performance is investigated. Characterization studies involving BET, XRD, TEM and H2 -TPR were also carried out to reveal the impact of metal entity and content on the structural, morphological and redox characteristics of the catalysts. The catalytic results imply that the de-N2 O performance is in general increased upon increasing metal loading, a fact being more intense over Ir-based catalysts. Under oxygen deficient conditions, N2 O conversions as high as ∼100% and ∼80% are reached at 600 °C over Ir- and Pd-based catalysts, respectively, instead of only ∼30%, achieved over Pt-based catalysts. A moderate degradation in oxygen excess conditions is observed with Ir and Pd catalysts, while Pt-based catalysts are almost fully depressed. The superior de-N2 O performance of Ir-, Pd-based catalysts can be mainly interpreted by taking into account the formation of metal oxide phases, not easily susceptible to oxygen poisoning. For Ir-based catalysts the active phase seems to be mainly the metal oxide phase (IrO2 ), as revealed by H2 -TPR, XRD and TEM experiments. In the case of palladium catalysts two different metal phases, i.e. PdO and metallic Pd 0 were detected. On the other hand, platinum catalysts presented only metallic Pt 0 species, which are prone to poisoning by strongly adsorbed oxygen atoms.